Vehicle speed monitoring system using Arduino and speed sensor - kumar C S, Kishor; K.V, Chandrashekar; A, Nikitha; B, Monisha; Appaji, Impana (IJRDO -Journal of Computer Science Engineering, 2017)
A smart vehicle speed monitoring system is proposed using arduino and speed sensor. Considering the roadsafety a new technique is described to identify the speeding vehicle and charge them fine for breaking the rules orintimating the consulted authority to take action. In past, lot of devices to detect rash driving on highways hasbeen made. Most of the approaches require human concentration and involve a lot of effort, which is difficult to implement.In this paper we intend to design a system aimed at early detection and alert of dangerous vehicle driving patterns it washelpful parents because know days most of accident was caused by college student by over speed .by installing our devicein bike we can get the speed of the vehicle if the vehicle cross the speed limit ,in our device we are using speed sensor todetect the vehicle speed and arduino to monitor the speed it will check the vehicle if the vehicle cross speed then it willintimate gsm board to send speed information to consulted authorities like parents or consulted person which we are specifyby owner of the vehicle .